Investigating the possibility of using an AR mask to support online psychological counseling - Noh, H; Go, J; Song, S; Kim, S; Kang, Y (Association for Computing Machinery, 2024)
Mental health problems are prevalent issues in modern society. While psychological counseling has been a traditional solution, it faces such barriers as negative societal perceptions and limited accessibility. To overcome these, researchers have explored remote counseling via video/voice calls. Despite its advantages of accessibility, convenience, and anonymity, the lack of personal interaction continues to be a drawback. This study investigates the feasibility of using an augmented reality (AR) mask in remote counseling and whether it could increase the level of self-disclosure-which is often used to measure the effectiveness of counseling-while maintaining anonymity. We conducted a controlled experiment and a qualitative user study to assess the effects of AR masks on counselees' level of self-disclosure during remote counseling. The results suggest that AR masks can increase this level more effectively for people with a low disposition for self-disclosure.